Ekstrak Batang Sipatah-Patah Meningkatkan Proliferasi dan Diferensiasi Sel Punca Mesenkimal Sumsum Tulang (CISSUS QUADRANGULA SALISB STEM EXTRACT INCREASED PROLIFERATION AND DIFFERENTIATION OF RATS BONE MARROWMESENCHYMAL STEM CELL) - Ceriana, Ria; Djuwita, Ita; Wresdiyati, Tutik (Jurnal Veteriner; Vol 15 No 4 (2014), 2015)
Acehnese people uses Cissus quadrangula (CQ) Salisb stem traditionally for treatment of variousbone disease. can differentiate into many different cell types such as osteoblast, adipocyteand chondrocytes.A study was conducted to determine the potential uses and the optimal dosage of C. quadrangula(CQ)extractin increasing the proliferation and differentiation of Mesenchymal stem cells derived from bone marrowof rat osteocytes. Mesenchymal stem cells were isolated from femoral and tibial rat bone marrow. Thecells were cultured according to the experimental group consisting of five the treatment groups each ofwhich has 4 replication. The cells were cultured in modified Dulbecco’s modified eagles’s medium (mDMEM).Control were cultured in medium without Cissus quadrangula Salisb stem extract whereas the treatmentgroup were cultured in medium with k 0,1 mg/mL, 0,3 mg/mL, 0,6 mg/mL, dan 0,9 mg/mLCissus quadrangulaSalisb stem extract. The level of the cell proliferation was determined by populationdoubling time (PDT) method. Cell differentiation was determined by counting cells and determining the diameter of osteoblastdan osteocytes.The result showed that CQ stem extract reduced PDT valuesignificantly (P<0,01) ascompared to those of control group. This showed that CQ stem extract increased the rat bone marrow stemcells. The number of h osteoblast in control group were significantly lower than those in CQ stem extracttreatment groups. The highest osteocyte population was observed in 0,3 mg/mL CQ extract treatmentgroup. The CQ stem extract can increase differentiation and proliferation of rat bone marrow masenchymalstem cells into osteoblastand osteocytes with the optimal dose of 0,3 mg/mL.
Keywords: Cissus quadrangula Salisb., stem cells, rat, bone marrow mesenkimal, proliferasi, diferensiasi